Penerapan Media Audio Visual untuk Meningkatkan Hafalan Surah-Surah Pendek di PAUD Al-Fitrah Jaya Asri Jayapura - Aisya Fitri Pratama; Hasruddin Dute; Moh. Ali Mahmudi; Zaidir Zaidir (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2024)
The objective of this study is to evaluate the effectiveness of audiovisual and interactive media in improving the memorization of short surahs among early childhood students at PAUD Al-Fitrah Jaya Asri, Jayapura City, and to investigate its influence on children's motivation and memory retention. The study utilized a descriptive qualitative methodology, incorporating participants including the principal, Islamic Education teachers, and parents. Data were collected by direct observation, in-depth interviews, and documentation, while data analysis followed the Miles and Huberman paradigm, which included data reduction, data presentation, and conclusion development. The results show that using animated movies as audiovisual aids to help kids remember short surahs greatly improved their interest, focus, and ability to remember. Children were able to remember and recite the surahs more readily and with better pronunciation (makharijul huruf) than with traditional techniques of becoming used to them. Also, using this media made parents more involved in the muroja’ah (review) process at home, which helped connect what students learned at school with what they learned at home. Some children needed a lot of help, but audiovisual media turned out to be a beneficial and unique way to learn. This study finds that audiovisual media is a relevant and effective teaching approach for enhancing the memorization of short surahs in early childhood learners, provided there is suitable monitoring and careful planning to meet the developmental requirements of children.